PENCIPTAKAN MINAT WORDS OF MOUTH YANG POSITIF PADA COMMERCIAL BANKING CENTER JAWA TENGAH - Jelita, Ronarata Novarina (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2015)
This research is done based on phenomena that occuied because of research result differences (research gap) about customer satisfaction and positive words of mouth in marketing. Besides, there are also research problem about customers satisfaction that decrease in banking industry, impacting number of customers decrease too, so that company in banking industry must improving their service quality to increase customers satisfaction. The impact from good customers satisfaction will give a positive effects in a way to increase positive words of mouth recording with the aim to increase number of customers.Some condition and factor above were importance to be checked empirically and analyzed. Theréfore the practitioner / managerial in bani‹ing industry can obtain facts to support them in making decision and good strategy for their company. This research is done fry taking resea/c/› object at one of business unit in PT. Bank Mandiri (Persero) Tbk, Commercial Banking Cen/er Jawa Tengah, amounting to 164 customers within. \Mith the number of 164 customers, very possibles to do a sensus to all of the customers, so that all of the customers become a respondense. Analysis technique that used to interpret and analyze data ini this research is technique of Structural Equation Model (SEM) of software package AMOS.Result examination proven hypothesis that factors core service quality and peripheral service quality become positlVé CiffeCt DI CUStOlTlers satisfaction, and futhermorre customers satisfaction become positive effect of positive words of mouth. It is mean high significance of each other variables. As for model which is raised in this research can he accepted posed at by index according to where value of GFI 0,933 , value of chi-square 58,951 , probability value 0,053 , value of TLI 0,983 and value of CFI 0,986 , all have up tc siandarci, although of A GFI 0,897 accepted by marginal.